The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1126/science.290.5491.509
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Daily Clouds on Titan

Abstract: We have discovered frequent variations in the near-infrared spectrum of Titan, Saturn's largest moon, which are indicative of the daily presence of sparse clouds covering less than 1% of the area of the satellite. The thermodynamics of Titan's atmosphere and the clouds' altitudes suggest that convection governs their evolutions. Their short lives point to the presence of rain. We propose that Titan's atmosphere resembles Earth's, with clouds, rain, and an active weather cycle, driven by latent heat release fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 30 publications
(18 reference statements)
9
93
0
Order By: Relevance
“…In Titan's southern hemisphere, clouds appear near the pole and at −40 • latitude (Griffith et al 1998(Griffith et al , 2000Brown et al 2002;Roe et al 2002;Gibbard et al 2004;Roe et al 2005;Ádámkovics et al 2006;Schaller et al 2006aSchaller et al , 2006bHirtzig et al 2006;Rodriguez et al 2009). Their hourly temporal evolution, cumuli structures, and positions in the upper troposphere, at ∼25-45 km, indicate that they consist of methane (the second most abundant atmospheric constituent), form through convection, and dissipate through rainfall (Griffith et al 2000;Porco et al 2005;Griffith et al 2005;Turtle et al 2009). Titan's northern hemisphere displays an increasing number of similarly discrete clouds, hypothesized to result from evaporation (Brown et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Titan's southern hemisphere, clouds appear near the pole and at −40 • latitude (Griffith et al 1998(Griffith et al , 2000Brown et al 2002;Roe et al 2002;Gibbard et al 2004;Roe et al 2005;Ádámkovics et al 2006;Schaller et al 2006aSchaller et al , 2006bHirtzig et al 2006;Rodriguez et al 2009). Their hourly temporal evolution, cumuli structures, and positions in the upper troposphere, at ∼25-45 km, indicate that they consist of methane (the second most abundant atmospheric constituent), form through convection, and dissipate through rainfall (Griffith et al 2000;Porco et al 2005;Griffith et al 2005;Turtle et al 2009). Titan's northern hemisphere displays an increasing number of similarly discrete clouds, hypothesized to result from evaporation (Brown et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous cloud features have also been detected from ground-based observations (e.g. Griffith et al 2000) and Cassini observations (Griffith et al 2005(Griffith et al , 2006Porco et al 2005). Even though some of the observed features have been speculated to be indicative of cryovolcanic activities (Roe et al 2005), most of the observed features can be understood in the framework of the general circulation model of Titan's atmosphere (Rannou et al 2006;Rodriguez et al 2007) and do not require any particular activity on Titan's surface.…”
Section: Observational Constraints On the Evolution Of Titan And Its mentioning
confidence: 99%
“…Neither, it seems, are dry places in the solar system. No clearly starred papers here, but we read about lavas made of water ice on Ganymede (Schenk et al 2001) and hydrated rocks as well (McCord et al 2001), ocean survival on Callisto , and rain on Titan (Griffith et al 2000). Admittedly, the rain drops are liquid methane, but the methane in turn comes from methane hydrate (Loveday et al 2001).…”
Section: Moons and Planets: Dry And Wet Countiesmentioning
confidence: 99%